Smart system for monitoring ammonium nitrate storage warehouse - Maha Khalil Ibrahim; Nadia Mahmood Hussien; Saad Najim Alsaad (Institute of Advanced Engineering and Science, 2021)
Ammonium nitrate (AN, NH4NO3) is one of the materials used in chemical industry and in agriculture. AN is not considered a fire risk but it is a strong oxidizing agent that can lead to fire and explosion, so, the ammonium nitrate must be stored under specific environmental conditions to avoid the occurrence of dangerous situations. In this paper, a smart monitoring system for Ammonium nitrate storage is developed. The system consists of three-parts: monitoring chemicals system part (MCS), warehouse monitoring part (WMP), and emergency part (EP). MCS includes several hardware components: Arduino microcontroller, Ds18b20 sensor, MQ sensors, system for mobile communication (GSM), global position system (GPS), buzzer, and LCD. Two types of alarms are designed, the first one is for the WMP that to receive the alarm when temperature is exceeds than a specific threshold in chemical warehouse. The second one is for EP. It represents the receiver part to receive the alarm with the location of the place that indicates to certain gases leakage that could cause a fire or explosion. Also, a buzzer is listening and display the sensor state on LCD. The system follows the object-oriented software engineering (OOSE) approach using unified modeling language (UML).